Age-Dependent Trends in the Celiac Disease: A Tertiary Center Experience. Issue 6 (June 2021) - Krauthammer, Alexander; Guz-Mark, Anat; Zevit, Noam; Marderfeld, Luba; Waisbourd-Zinman, Orith; Silbermintz, Ari; Mozer-Glassberg, Yael; Nachmias Friedler, Vered; Rozenfeld Bar Lev, Michal; Matar, Manar; Assa, Amit; Shamir, Raanan
ABSTRACT: Objectives: Celiac disease (CD) is a common intestinal autoimmune disorder with diverse presenting features. We aimed to determine age-dependent patterns in CD presentation, diagnosis and management at a large tertiary referral center. Methods: A retrospective review of electronic medical records of pediatric patients diagnosed with CD between January 1999 and December 2018 at Schneider Children's Medical Center of Israel. We compared demographics, clinical and laboratory parameters between four age groups at CD presentation. Results: A cohort of 932 children was divided into four groups by age (in years) at diagnosis: 0–3 (17.9%), 3–6 (31.8%), 6–12 (34.5%), 12–18 (15.8%). The youngest age group presented more frequently with diarrhea, weight loss, abdominal distention, vomiting and lower weight z scores, P < 0.01. Hypoalbuminemia and zinc deficiency were also more frequent in this age group, compared to older patients ( P < 0.05, each). Rates of anemia were higher in younger age groups (0–3 and 3–6 years), compared to older age groups, P < 0.05. Patients in the younger age groups (0–3 and 3–6 years) presented more frequently with tissue transglutaminase (TTG) levels above 10 times the upper limit of normal (ULN; P < 0.05), and more often normalized their CD serologies by 24 months of gluten-free diets (GFD) compared to older age groups ( P < 0.05). Conclusion: There is an age-dependent variation in CD presentation during childhood. Younger patients present more often with malabsorptive features, and higher TTG levels, yet normalize TTG while on GFD more rapidly than older patients. Clinicians should be aware of the diversity in CD presentation and course at the various presentation age. Abstract : Supplemental Digital Content is available in the text